The finding of Biomphalaria glabrata (Say, 1818) in two counties of S.Paulo State, Brazil - Teles, Horácio Manuel Santana (Revista de Saúde Pública, 1986)
This study reports the finding of Biomphalaria glabrata (Say, 1818) in two counties of the State of S. Paulo (Brazil): in the capital (S.Paulo) itself and in Ribeirão Preto. In the former melanic snails were collected from the Billings reservoir, in the latter collection was made of albinic specimens which had established a colony in an aquarium.